Facebook : the missing manual - Vander Veer, Emily A. (Sebastopol, Calif. : O'Reilly, 2011)
With this guide, learn how to unlock Facebook's talents as personal website creator, souped-up address book, and bustling community forum. It will help you get the most out of your Facebook experience.--[book cover].
'The book that should have come with the site.'
Includes index.
Keywords: Facebook (Firm).; Facebook (Electronic resource).; Web sites -- Design; Online social networks; Social networks -- Computer network resources